Evolution of a key enzyme of aerobic metabolism reveals Proterozoic functional subunit duplication events and an ancient origin of animals - Christopher Coates (Scientific Reports, 2021)
The biological toolkits for aerobic respiration were critical for the rise and diversification of early animals. Aerobic life forms generate ATP through the oxidation of organic molecules in a process known as Krebs’ Cycle, where the enzyme isocitrate dehydrogenase (IDH) regulates the cycle's turnover rate. Evolutionary reconstructions and molecular dating of proteins related to oxidative metabolism, such as IDH, can therefore provide an estimate of when the diversification of major taxa occurred, and their coevolution with the oxidative state of oceans and atmosphere. To establish the evolutionary history and divergence time of NAD-dependent IDH, we examined transcriptomic data from 195 eukaryotes (mostly animals). We demonstrate that two duplication events occurred in the evolutionary history of NAD-IDH, one in the ancestor of eukaryotes approximately at 1967 Ma, and another at 1629 Ma, both in the Paleoproterozoic Era. Moreover, NAD-IDH regulatory subunits β and γ are exclusive to metazoans, arising in the Mesoproterozoic. Our results therefore support the concept of an ‘‘earlier-than-Tonian’’ diversification of eukaryotes and the pre-Cryogenian emergence of a metazoan IDH enzyme.